Pecandu Narkoba Sebagai Alasan Cerai Gugat: (Persepktif Hukum Islam dan Kompilasi Hukum Islam) - Umami, Hafidhul; Nizam Fauzida (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
Drug addiction has become a serious social problem that often disrupts family harmony and leads to divorce. This study examines drug addiction as a ground for divorce (cerai gugat) from the perspective of Islamic Law and the Compilation of Islamic Law (KHI) in Indonesia. According to Islamic Law, marriage is intended to build a peaceful, loving, and compassionate household (sakinah, mawaddah, wa rahmah). However, when one spouse becomes addicted to drugs, it can result in negligence of religious duties, moral decay, financial instability, and domestic violence—all of which contradict the objectives of marriage (maqāṣid al-nikāḥ). In such cases, divorce may be considered permissible (mubāḥ) or even necessary to prevent greater harm (mafsadah). Based on the KHI, particularly Article 116, drug addiction falls under the category of “one party committing continuous misconduct or moral degradation.” Therefore, both Islamic Law and the KHI recognize drug addiction as a valid legal and moral reason for a wife to file for divorce.